Analisis Pragmatik Fungsi Tindak Tutur dalam Kasus Ujaran Kebencian Ferdinand Hutahaen - Marjaya, Ahmad (RUANG KATA: Journal of Language and Literature Studies, 2023)
Speech is part of action. Making a statement incorrectly can lead someone into a case of hate speech. This study aims to describe speech acts in the speech of characters/people who are used as legal cases for hate speech. The results of this study are useful for helping the public to understand and provide knowledge to the public to be careful in speaking so as not to be subject to legal action for hate speech. This research uses descriptive qualitative research. The pragmatic analysis used is speech act analysis. The data for this study are uploads on social media Twitter from someone who has been sued for hate speech, namely Ferdinand Hutahaen. The results of this study are: the utterance is declarative in nature which affects the involvement of the utterance in the lawsuit. Hate speech is a choice of language that has a negative connotation in expressing the speaker's opinion about something.Keywords: pragmatics; speech act; hate speech.